1988
DOI: 10.1177/002246698802100407
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Directional and Cross-Categrical Social Status of Learning Disabled, Behaviorally Disordered, and Nonhandicapped Adolescents

Abstract: fered from a larger nonhandicapped population in several aspects of bi-directional social status. In cross-categorical comparisons of assigned social status, the three groups did not differ significantly. With regard to cross-categorical received status, however, the comparison groups varied widely. Findings are discussed with regard to similarities and differences among mildly handicapped individuals, and the need to consider all aspects of their social interrelations.at DALHOUSIE UNIV on June 21, 2015 sed.sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In a recent study of attitudes toward inclusion in middle school, Siperstein, Parker, Bardon, and Widaman (2007) found that early adolescents without disabilities reported relatively little contact with students with intellectual disabilities either in their classes or in the school; and only 40% or less indicated that they were willing to have social contact with peers with intellectual disabilities outside of the school setting. This finding is consistent with reports from studies conducted in high schools 2 decades earlier which showed that students with intellectual disabilities and students with behavioral disorders (Sabornie, Kauffman, Ellis, Marshall, & Elksnin, 1987) tended to have lower rates of social acceptance as compared to their peers without disabilities, whereas students with learning disabilities were found to be similar in acceptance to their classmates without disabilities (Sabornie & Kauffman, 1986). Further, studies that have examined teacher ratings of the social behavior of adolescents have suggested that many high school students with disabilities may have social competence problems that contribute to their low social acceptance (Cullinan & Sabornie, 2004;Lane, Carter, Pierson, & Glaeser, 2006;Sabornie, Cullinan, Osborne, & Brock, 2005).…”
Section: S O C I a L R E L A T I O N S O F A D O L E S C E N T S W I T H D I S A B I L I T I E Ssupporting
confidence: 93%
“…In a recent study of attitudes toward inclusion in middle school, Siperstein, Parker, Bardon, and Widaman (2007) found that early adolescents without disabilities reported relatively little contact with students with intellectual disabilities either in their classes or in the school; and only 40% or less indicated that they were willing to have social contact with peers with intellectual disabilities outside of the school setting. This finding is consistent with reports from studies conducted in high schools 2 decades earlier which showed that students with intellectual disabilities and students with behavioral disorders (Sabornie, Kauffman, Ellis, Marshall, & Elksnin, 1987) tended to have lower rates of social acceptance as compared to their peers without disabilities, whereas students with learning disabilities were found to be similar in acceptance to their classmates without disabilities (Sabornie & Kauffman, 1986). Further, studies that have examined teacher ratings of the social behavior of adolescents have suggested that many high school students with disabilities may have social competence problems that contribute to their low social acceptance (Cullinan & Sabornie, 2004;Lane, Carter, Pierson, & Glaeser, 2006;Sabornie, Cullinan, Osborne, & Brock, 2005).…”
Section: S O C I a L R E L A T I O N S O F A D O L E S C E N T S W I T H D I S A B I L I T I E Ssupporting
confidence: 93%
“…But in this case, it is necessary to accept that we and those we interact with do not go out of the watch list and that none of us will change. When the classroom behaviors of special education teachers were examined, the dominant metaphor was "management" (Sabornie et al, 1988). Those who do not comply with the boundaries drawn by the curriculum are perceived as "out of control," and teachers have the belief that "The student must follow the rules of the teacher, the rules of the system so that he can get well" (Reid et al, 1994).…”
Section: The Contributions Of the Active Learner To Himselfmentioning
confidence: 99%
“…Cullinan and Epstein (1985) found distinctions based on patterns of maladjustment, whereas Sabornie, Kauffman, Ellis, Marshall, andElksnin (1987-1988) reported differences across these groups in terms of assigned and received social status. In fact, much of the existing research challenges this assumption, especially when students with learning disabilities are compared to students with behavioral disorders.…”
mentioning
confidence: 99%